Pembinaan Literasi Baca Pada Anak-Anak dengan Metode CABACA di Desa Kanrung Kec. Sinjai Tengah Kab. Sinjai - Ni'mah, Siar; Haslinda, Haslinda; Umar, Umar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Education makes a person get information and also community members, especially elementary school children, are future assets. Therefore, it is necessary to develop reading and writing. One way to carry out reading and writing coaching is to use the CABACA book media. The purpose of using CABACA media is to make it easier for students to recognize letters, spell words, read words, and read sentences. The purpose of this training is to reduce the illiteracy of students in Kanrung Village, especially students at SDN No 213 Sabbang by coaching learning to read and to write in school. The type of CABACA method used is phenomenological research with a qualitative approach located in Kanrung Village, Central Sinjai District, Sinjai Regency, while the data collection techniques used were interviews, observation and documentation. The results of fostering learning to read and write using CABACA media can reduce illiteracy and improve the reading ability of students in Kanrung Village.